SYNTHESIS MATERIAL OF ZEOLITE NANOPOROUS (ZSM-5) FROM COAL FLY ASH - Purwasasmita, Bambang Sunendar; Kurnia, Agung; Wibowo, Arie (Jurnal Zeolit Indonesia, 2010)
Coal fly ash (CFA) is the waste of coal usage that requires serious attention on handling because it is have the large quantity and containing a dangerous substances for environmental. The interesting method of waste processing of CFA is using CFA as zeolite raw material because CFA have a rich silicate and alumina. In this study, CFA is used as a raw material for zeolite synthesis nanoporous (ZSM-5) so that expected could be a solution for waste processing of CFA and also could be deliver a valuable materials that needed on many applications. Based on the result of characterization XRD and SEM, was known that structure of ZSM-5 and other zeolites (Na12Al12Si12O48.27H2O and Na0,3Al2,564Si100O203,996) have been successfully synthesized on hydrothermal processing at temperature of 97Â°C and the pressure of 1,3 bar.